Translation and psychometric validation of the Chinese version of the metacognitive awareness scale among nursing students - Li, Shasha; Xu, Jun; Jia, Xuejing; Zhao, Yanjun; Liu, Xiaojing; Wang, Yuecong (Frontiers in Psychology, 2024)
Objective This study endeavors to translate and psycho-metrically validate the metacognitive awareness inventory scale (MAS) for nursing students in China. Method A total of 592 nursing students were enlisted from four universities situated in the eastern, southern, western, and northern regions of China. Content validity and reliability were evaluated using the content validity index and item-total correlation coefficient, and Cronbach’s alpha coefficients, respectively. Convergent validity examined the goodness of fit among sub-scales through the average extracted variance and composite reliability. Results Exploratory factor analysis confirmed the first-order and second-order factor models, contributing to a cumulative variance of 89.4 and 59.5%, respectively. The Cronbach’s alpha values were 0.963 and 0.801, respectively. Confirmatory factor analysis outcomes indicated an excellent overall fit index for the model, satisfying the convergent validity criteria and achieving a target coefficient of 96.0%, which is consistent with the original scale structure. Conclusion The Chinese version of the MAS (C-MAS) is a reliable and valid instrument for assessing metacognitive awareness among Chinese nursing students. Further research should consider a broader sample of nursing students across China to reinforce the scale’s applicability.